Mixed Learning with a Project Based Learning (PjBL) approach in Raid Planning Execution (RPE) Training Courses - Eveline Siregar; Suyitno Muslim; Dita Hendrani (Indonesian Journal Of Educational Research and Review, 2022)
The rapid development of technology demands a system that is fast, easy, cheap, effective and efficient and can be accessed anytime and anywhere, including in the world of education and training. This study aims to produce online learning plans with a Project Based Learning (PjBL) approach and online learning media that can be used in Raid Planning Execution (RPE) training courses. This study uses the Research and Development (R n D) method with the Integrative Learning Design Framework (ILDF) development model and the PEDATI development design model (Learn, Learn, Apply and Evaluation). Subject of this study involve ten personnel in the field of eradication of Human Resources Development of the National Narcotics Agency. Sample selection is done randomly. The stages carried out including one-to-one evaluation by experts (expert review), one-to-one evaluation by training participants (one to one) and small group evaluation. To obtain information on the effectiveness of the resulting product, an effectiveness test was conducted. The results of this study indicate that online learning plans with a project-based learning approach and online learning media are appropriate for use in Raid Planning Execution (RPE) training courses.